2018
DOI: 10.3389/fpsyg.2018.01102
|View full text |Cite
|
Sign up to set email alerts
|

The Contagion of Unethical Pro-organizational Behavior: From Leaders to Followers

Abstract: Unethical pro-organizational behavior is a common phenomenon in businesses, and one that can cause great damage to them as well as to wider society. Although prior studies have investigated why individuals engage in unethical pro-organizational behavior, little research has been undertaken into why such behavior might be commonplace in organizations. The present study focuses on the downstream contagion of unethical pro-organizational behavior from leaders to followers. Drawing on social identity theory, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 53 publications
(83 reference statements)
1
31
0
Order By: Relevance
“…The present study builds on this emergent literature and also responds to the call for exploring the mechanisms underlying the relationship between supervisor UPB and employee UPB (Zhang et al, 2018). The cognitive and psychological processes that underlie and influence the cause and effect relations of workplace behaviors are intrinsically important relative to theory development (Bargh & Ferguson, 2000;Moore et al, 2012;Moore & Gino, 2015;Tenbrunsel & Smith-Crowe, 2008;Treviño et al, 2006).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The present study builds on this emergent literature and also responds to the call for exploring the mechanisms underlying the relationship between supervisor UPB and employee UPB (Zhang et al, 2018). The cognitive and psychological processes that underlie and influence the cause and effect relations of workplace behaviors are intrinsically important relative to theory development (Bargh & Ferguson, 2000;Moore et al, 2012;Moore & Gino, 2015;Tenbrunsel & Smith-Crowe, 2008;Treviño et al, 2006).…”
mentioning
confidence: 88%
“…Such antecedents include employee attitudes such as organizational affective commitment (Matherne & Litchfield, 2012), organizational identification (Effelsberg et al, 2014;Umphress et al, 2010), and psychological entitlement (Lee et al, 2019); leader behaviors such as ethical leadership (Miao et al, 2013;Wang & Li, 2019), transformational leadership (Effelsberg et al, 2014;Graham et al, 2015), and responsible leadership (Cheng et al, 2019); and organizational characteristics such as ethical organizational climate (Miao et al, 2013). Additionally, Fehr et al (2019) and Zhang et al (2018) demonstrated that supervisor UPB is positively associated with subordinate UPB.…”
mentioning
confidence: 99%
“…Previous studies have studied the antecedents of unethical pro-organizational behavior from the perspectives of individual characteristics (such as psychological rights, moral identity, moral disengagement, the high performance expectation, and the high performance pressure; Wu et al, 2016a ; Chen and Liang, 2017 ; Zhao and Zhou, 2017 ; Lee et al, 2019 ), leadership style and behavior (such as transformational leadership, and moral leadership; Miao et al, 2013 ; Effelsberg et al, 2014 ; Zhang et al, 2018 ; Wang and Li, 2019 ), and colleague behavior ( Thau et al, 2015 ). However, it is worth noting that employees often engage in unethical pro-organizational behavior for the sake of organization’s short-term interests.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, moral identity is an important concept of moral cognition that stimulates ethical behavior (Aquino et al, 2009), and if followers have different levels of moral identity, their behaviors might also differ. Y. Zhang et al (2018) demonstrated that moral identity could weaken the effects of a leader’s UPB on a follower’s UPB.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Y. Zhang et al (2018) demonstrated that moral identity could weaken the effects of a leader's UPB on a follower's UPB. From the analysis above, we infer that followers with high moral identity under benevolent leadership will engage in less UPB, and we propose the following hypothesis:…”
Section: The Moderating Role Of Moral Identitymentioning
confidence: 99%